2023
DOI: 10.1097/sla.0000000000006082
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Neighborhood Disadvantage on High-Risk Oncotype DX Recurrence Scores and Breast Cancer Survival

Neha Goel,
Alexandra Hernandez,
Deukwoo Kwon
et al.

Abstract: Objective: Evaluate the association between neighborhood disadvantage and Oncotype DX score, a surrogate for tumor biology, among a national cohort. Summary Background Data: Women living in disadvantaged neighborhoods have shorter breast cancer (BC) survival, even after accounting for individual-level, tumor, and treatment characteristics. This suggests unaccounted social and biological mechanisms by which neighborhood disadvantage may impact BC surviva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 54 publications
(118 reference statements)
0
1
0
Order By: Relevance
“…11 For instance, studies evaluating structural racism through measures of socioeconomic and neighborhood disadvantage have demonstrated that greater neighborhood level deprivation is associated with more aggressive breast cancer subtypes and unfavorable tumor genomics. [22][23][24][25] This study is limited by its retrospective design. Likewise, our results are limited by the variables provided through SEER.…”
Section: Discussionmentioning
confidence: 99%
“…11 For instance, studies evaluating structural racism through measures of socioeconomic and neighborhood disadvantage have demonstrated that greater neighborhood level deprivation is associated with more aggressive breast cancer subtypes and unfavorable tumor genomics. [22][23][24][25] This study is limited by its retrospective design. Likewise, our results are limited by the variables provided through SEER.…”
Section: Discussionmentioning
confidence: 99%